1969
DOI: 10.1161/01.res.24.2.213
|View full text |Cite
|
Sign up to set email alerts
|

Hepatic Clearance of Renin in Canine Experimental Models for Low- and High-Output Heart Failure

Abstract: Hepatic blood flow, hepatic extraction of renin, and hepatic clearance of renin were compared in normal conscious dogs, in dogs with constriction of the thoracic inferior vena cava (as a model of low-output heart failure), and in dogs with an aortic-caval fistula (high-output heart failure). Both "failure" preparations showed marked sodium retention. Renin was measured by methods described previously and expressed as nanograms of angiotensin produced during incubation per milliliter of plasma. Hepatic plasma f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
16
0

Year Published

1970
1970
1992
1992

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 29 publications
(16 citation statements)
references
References 20 publications
0
16
0
Order By: Relevance
“…Plasma renin activity was frequently elevated and the increase for the group was statistically significant; it seems unlikely that the occasional normal value observed was related to the level of sodium intake since this was constant. Also, our earlier studies (12,19) have been done at this level of sodium intake and there was no evidence that it depresses plasma renin activity. Consequently, the findings in dogs and the observations on women suggest that plasma renin activity varies from a normal level to an elevated one during pregnancy.…”
Section: Introductionmentioning
confidence: 86%
See 1 more Smart Citation
“…Plasma renin activity was frequently elevated and the increase for the group was statistically significant; it seems unlikely that the occasional normal value observed was related to the level of sodium intake since this was constant. Also, our earlier studies (12,19) have been done at this level of sodium intake and there was no evidence that it depresses plasma renin activity. Consequently, the findings in dogs and the observations on women suggest that plasma renin activity varies from a normal level to an elevated one during pregnancy.…”
Section: Introductionmentioning
confidence: 86%
“…These considerations raise the question of the possible role of estrogens in increasing aldosterone secretion by a nonrenin mechanism. There is also the possibility of a decrease in renin metabolism by the liver (19) as a contributory mechanism to the high plasma renin activity, but no data are available on this point. There remains the question of whether the high plasma level of estrogens achieved during exogenous hormone administration is present during pregnancy.…”
Section: Introductionmentioning
confidence: 99%
“…Thus it has been suggested that the liver is the major site of renin metabolism. [1][2][3][4][5][6] This observation is supported by the finding that reduced hepatic blood flow induces a marked increase in arterial renin by an elective decrease in hepatic extraction of renin. 1,2,7 It has also been reported that following hepatic damage due to carbon tetrachloride intoxication in dogs, the difference between PRA values in hepatic and portal veins is no longer appreciable.'…”
Section: Introductionmentioning
confidence: 75%
“…Blood was drawn from the jugular vein (10 ml) and collected in ethylenediamine tetraacetate (EDTA) for the determination of plasma renin activity by the technique described by Schneider et al (3). A 3-hour incubation was done and the amount of angiotensin II formed assayed in the vagotomized, ansolysin-treated rat.…”
Section: Methodsmentioning
confidence: 99%